Exploration of RNAi-based therapeutic strategies for dominantly inherited disorders - Allen, Danny (Trinity College (Dublin, Ireland). Department of Genetics, 2006)
The primary aim of this thesis was to explore genetic agents with the ability to suppress expression of certain gene products i.e. those involved in the etiology of dominant disorders such as osteogenesis imperfecta (OI) and dominant dystrophic epidermolysis bullosa (dDEB). OI and dDEB are inherited in an autosomal dominant fashion and have a high level of intragenic heterogeneity. Over 150 and 80 mutations in the COL1A1 and COL1A2 genes respectively are known to give rise to OI and over 200 mutations have been reported in the COL7A1 gene in dDEB patients. Given this mutational diversity a mutation-independent therapeutic approach using ribozymes and RNAi interference (RNAi) is being developed. This approach follows a suppression and replacement strategy previously described. The focus of the study described here is the design, generation and evaluation of key elements of this therapeutic approach.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin